Empowerment of Coastal Communities in Increasing Income Through Seaweed Kappaphycus Alvarzii Cultivation Activities in Bulukumba Regency - Nur, Darmawis; Rustam, Rustam; Asni, Andi (AgriSains, 2019)
This study aimed to examine efforts to empower coastal seaweed farmer communities, the level of business feasibility and income of coastal seaweed farmers in Bulukumba Regency. Data collection was conducted through literature studies, and field studies (interviews, observations and documentation). The number of respondents was 100 persons. The results showed that the seaweed cultivation business in Bulukumba Regency was feasible to be carried out with a total income of Rp. 42.675.000/year. Analysis of revenue-cost (R/C) obtained value (R/C) of dried seaweed of 2,23. Break event point (BEP) analysis obtained a break-even point at the selling price of Rp. 4.333/kg, return on investment (ROI) analysis obtained a value of 2,23%. The coefficient of determination (R2) showed the contribution of planning, handling, and marketing variables to the level of income of seaweed cultivation (Y) in Bulukumba Regency which was 68,9% while 31,1% was influenced by other factors.Keywords: Business Feasibility, Seaweed, Empowerment.